ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RASIONALITAS KENAIKAN PAJAK BUMI DAN BANGUNAN DI KOTA SUKABUMI - Acep Suherman; Andri Indrawan; Tina Kartini (Jurnal Bina Akuntansi, 2023)
Land and building tax is local revenue that is collected from the community for land and building ownership. The rationality of the people in this study is shown in the form of public awareness in accepting and paying land and building taxes. The purpose of this study is to explain how people are invited to participate rationally in increasing land and building taxes and being obedient in paying taxes. The research method used in this study uses quantitative methods. The results of the statistical test show that the variable bearing power has a positive and significant effect on the awareness as well as the benefits of taxes variable which has a positive and significant effect on the awareness as a manifestation of community participation and mutual cooperation under Development.